Taxonomic status of the endemic South African bamboo, Thamnocalamus tessellatus - Thomas R. Soderstrom; R. P. Ellis (Bothalia: African Biodiversity & Conservation, 1983)
Thamnocalamus tessellatus (Nees) Soderstrom & Ellis, [= Arundinaria tessellata (Nees) Munro] is the only endemic South African bamboo and occurs from the eastern districts of the Cape, through Lesotho and Natal, to the eastern Orange Free State at elevations of about 1 500-2 500 m. The Mountain Bamboo, or ‘Bergbamboes’ was first described by Nees in 1841 as a member of the genus Nastus because of the similarity, to him, of the spikelets between it and N. barbonicus, but was later transferred to the all-encompassing genus of the time, Arundinaria, the type species of which is endemic to the southeastern United States of America. Based on our present knowledge of bamboo genera, this South African species may be excluded from Nastus because the inflorescence is not a panicle but bracteate racemiform, the vegetative branches do not arise in a verticillate manner but are a series of subequal branches that are borne in a row above the nodal line and T. tessellatus has an androecium of three stamens and not six as in Nastus. The Bergbamboes, with sympodial rhizomes and branch complement of several subequal branches, can also not be maintained in Arundinaria, for monopodial rhizomes and a single branch at the node are typical of this genus. The simple, ebracteate, and exserted inflorescence of Arundinaria is also quite distinct from that of the Bergbamboes.